Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
S = \(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+.....+\frac{1}{2^{20}}\)
2S = \(1+\frac{1}{2}+\frac{1}{2^2}+.....+\frac{1}{2^{19}}\)
=> 2S - S = \(1-\frac{1}{2^{19}}\)
=> S = \(1-\frac{1}{2^{19}}<1\) (đpcm)
S=1/2+1/2^2+1/2^3+...+1/2^20
2S=1+1/2+1/2^2+....+1/2^19
=>2S-S=(1+1/2+1/2^2+...+1/2^19)-(1/2+1/2^2+1/2^3+...+1/2^20)
S=1-1/2^20<1
=>S<1
Vậy S<1
\(2S=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{19}}\)
\(2S-S=1-\frac{1}{2^{20}}\)
\(S=1-\frac{1}{2^{20}}< 1\)-> ĐPCM.
nen 2S=1+1/2+1/2 mu 2 +....1/2 mu 19
do do 2S-S=1-1/2 mu 20 .vay S=1-1/2 mu 20 <1
S=1/2+1/2^2+1/2^3+...+1/2^20
2S=1+1/2+1/2^2+....+1/2^19
=>2S-S=(1+1/2+1/2^2+...+1/2^19)-(1/2+1/2^2+1/2^3+...+1/2^20)
S=1-1/2^20<1
=>S<1
Vậy S<1